Very High Negative Concordance Rate of RT-PCR for SARS-CoV-2 in Nasopharyngeal Swab and Tracheo-Bronchial Aspirate in Children - Camporesi, Anna; De Silvestri, Annalisa; Diotto, Veronica; Ferrario, Stefania; Eccher, Laura; De Ferrari, Alessandra; Messina, Francesco; Pelizzo, Gloria; Mileto, Davide; Calcaterra, Valeria; Buonsenso, Danilo (Frontiers in Pediatrics, 2022)
Reliable testing methods for SARS-CoV-2 in children are essential to allow normal activities. Diagnosis of SARS-CoV-2 infection is currently based on real-time reverse transcriptase-polymerase chain reaction (RT-PCR) performed on nasopharyngeal (NP) swabs; concerns have been raised regarding NP swab accuracy in children to detect the virus because of potential lack of cooperation of the patients or due to general uncertainties about concordance between high and low respiratory tract specimens in children. The aim of the study (IRB approval: ST/2020/405) is to prospectively compare RT-PCR results on NP and tracheo-bronchial aspirate (TA) in children admitted to the hospital for surgery or admitted to the Pediatric Intensive Care Unit (PICU) of a tertiary children hospital in Milano, Italy, during a peak of Covid-19 infections in the city. 385 patients were enrolled in the study: 364 from surgical theatre and 21 from PICU. Two patients (0.5%) tested positive on tracheo-bronchial aspirate being were negative on NP; both cases occurred in November, 2020, during a peak of infection in the city. Specificity of NP swab was 0.995 (95% CI: 0.980-0.999). Two patients with positive NP swab tested negative at on tracheo-bronchial aspirate. Conclusion: our study shows that specificity of SARS-CoV-2 RT-PCR on TA swab, compared to results of SARS-CoV-2 RT-PCR on NP, was very high for negative cases in our pediatric cohort during a period of high epidemiological pressure.